Genetic associations between scrotal circumference and female reproductive traits in nelore cattle - Terakado, A. P.N. [UNESP]; Boligon, A. A.; Baldi, F. [UNESP]; Silva, J. A.V. [UNESP]; Albuquerque, L. G. [UNESP] (Oxford University Press (OUP), 2015)
The objective of this study was to estimate genetic associations between scrotal circumference obtained at 12 (SC12; mean of 21.46 ± 2.74 cm), 15 (SC15; mean of 25.31 ± 3.19 cm), and 18 mo of age (SC18; mean of 26.77 ± 2.95 cm) and reproductive traits measured directly in heifers (age at first calving [AFC]: mean of 1,062.06 ± 114.79 d; heifer pregnancy at 16 mo of age [HP]: mean of 15.4 ± 0.36%; and subsequent rebreeding of primiparous heifers [HR]: mean of 27.1 ± 0.44%) using Bayesian inference to evaluate the possible inclusion of these traits as selection criteria in beef cattle breeding programs. Genetic gains comparisons were also estimated. A total of 53,683 data of Nelore animals born between 1990 and 2006, obtained from the livestock archive of Agropecuária Jacarezinho Ltda. (Valparaíso, São Paulo, Brazil), were analyzed. Two-trait analysis provided heritability estimates of 0.35 ± 0.08, 0.40 ± 0.04, 0.37 ± 0.03, 0.21 ± 0.01, 0.55 ± 0.03, and 0.17 ± 0.03 for SC12, SC15, SC18, AFC, HP, and HR, respectively. The genetic correlations between scrotal circumference and AFC, HP, and HR were –0.42 ± 0.12, 0.43 ± 0.13, and –0.13 ± 0.17, respectively, for SC12; –0.25 ± 0.07, 0.26 ± 0.07, and –0.11 ± 0.10, respectively, for SC15; and –0.22 ± 0.06, 0.39 ± 0.06, and 0.11 ± 0.09, respectively, for SC18. The direct selection response for HP was 0.12%, but when HP is indirectly selected based on the scrotal circumferences, the gains on these correlated responses were higher (0.16, 0.16, and 0.22%) for selection based on SC12, SC15, and SC18, respectively. These findings suggest that the selection of animals for larger scrotal circumference, particularly at 12 mo of age, should result in higher rates of HP and younger AFC of Nelore females.
Keywords: Age at first calving; Bayesian inference; Beef cattle; Heifer pregnancy; Heifer rebreeding